APPLICATION OF PBL MODEL THROUGH CRT APPROACH TO IMPROVE MATHEMATICS LEARNING OUTCOMES OF CLASS X7 AT SMAN 2 MATARAM - Islami, Rismala; Amrullah; Wartana (Mandalika Mathematics and Educations Journal, 2025)
This study was motivated by the low learning outcomes of Class X students.7 SMAN 2 Mataram about mathematics, especially about material opportunities. The purpose of this study is to improve the outcome of mathematics learning through the application of Problem Based Learning (PBL) model with Cultural Responsive Teaching (CRT) approach. This study is a Class Action Research (PTK) conducted in two cycles in Class X.7 SMAN 2 Mataram with 37 students. Each cycle consists of stages of planning, implementation, observation, and reflection. The CRT approach is realized by integrating Lombok's local culture as a learning context, such as traditional Sasak (ngyongkolan) events and traditional snacks. Data collection is done through formative assessment in the form of questions that are done individually. The results showed an increase in student learning outcomes, seen from the increase in classical completeness from 8.11% in pre-cycle to 48.65% in cycle I, and reached 89.19% in Cycle II. Based on these results, it can be concluded that the application of PBL model with CRT approach is effective in improving students ' math learning outcomes on opportunity materials